2017
DOI: 10.1158/1078-0432.ccr-16-1121
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive IRAK4 Activation Underlies Poor Prognosis and Chemoresistance in Pancreatic Ductal Adenocarcinoma

Abstract: Purpose Aberrant activation of the NF-κB transcription factors underlies the aggressive behavior and poor outcome of pancreatic ductal adenocarcinoma (PDAC). However, clinically effective and safe NF-κB inhibitors are not yet available. Because NF-κB transcription factors can be activated by the Interleukin-1 Receptor-Associated Kinase (IRAK) downstream of the Toll-like receptors (TLRs), but has not been explored in PDAC, we sought to investigate the role of IRAK in the pathobiology of PDAC. Experimental Des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 45 publications
6
65
0
Order By: Relevance
“…Supporting our results using shRNAs, both IRAK4 inhibitors suppressed clonogenic growth of CRC cells ( Figure 5C). Notably, while IRAK4 inhibitors did not suppress growth of SW80 and SW620 cells in monolayer culture, they potently suppressed clonogenic growth of these cells, implying engagement and need for IRAK4 and NF-κB activation in stress-induced conditions, as we previously reported in pancreatic cancer cells (26). Both IRAK4 inhibitors potently blocked p-IRAK1, p-p50, nuclear translocation of p65, and NF-κB-driven luciferase reporter activity dose-dependently in CRC cells ( Figure 5, D-F).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Supporting our results using shRNAs, both IRAK4 inhibitors suppressed clonogenic growth of CRC cells ( Figure 5C). Notably, while IRAK4 inhibitors did not suppress growth of SW80 and SW620 cells in monolayer culture, they potently suppressed clonogenic growth of these cells, implying engagement and need for IRAK4 and NF-κB activation in stress-induced conditions, as we previously reported in pancreatic cancer cells (26). Both IRAK4 inhibitors potently blocked p-IRAK1, p-p50, nuclear translocation of p65, and NF-κB-driven luciferase reporter activity dose-dependently in CRC cells ( Figure 5, D-F).…”
Section: Resultssupporting
confidence: 60%
“…Antibodies used for IHC and immunofluorescence (IF) staining are provided in Supplemental Table 2. Unless otherwise specified, all IF quantification was performed under fluorescence or light microscopy on ten ×20-power fields per tumor, and data are presented as mean ± SEM, as previously described (26). For all TMA image analysis, whole slide tissue scans were obtained at ×20 magnification on a Zeiss Axio Scan Z1 Brightfield/Fluorescence Slide Scanner (resolution 0.645 μm per pixel).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…40 A number of studies demonstrated that IL-1-mediated constitutive activation of NF-kB occurs in pancreatic tumors, and is a requirement for tumor development. 16,[41][42][43] When we blocked IL-1R signaling with Anakinra (IL-1R antagonist), we found strong inhibition of IL-6 and CXCL8 production only in cells with epithelial phenotype. In vivo, Anakinra-treated mice had significant inhibition of tumor growth and lower infiltration of macrophages and vessels.…”
Section: E1388485-8mentioning
confidence: 89%